DAMPAK MOTIVASI, KARAKTER INDIVIDU PADA KEPUASAN KERJA DAN IMPLIKASINYA TERHADAP LOYALITAS - Zurlaini Damanik, Ayu Zurlaini; Girsang, Rosita Manawari; Sinaga, Satria Yohannes (Economic Development Progress, 2022)
The research objective was to analyze the impact of individual motivation and character on job satisfaction and its implications for loyalty at PT Indonesia Asahan Aluminum. This type of descriptive quantitative research. The population in the study were 40 employees of PT Indonesia Asahan Aluminum (Persero) smelter potline 1. Using saturated or census samples. Sampling method using nonprobability sampling. Data analysis was carried out through the SmartPLS program. The results of the study show that motivation has a direct effect on job satisfaction p-values ​​0.005. Individual character influences job satisfaction with p-values ​​of 0.004. Work motivation has an effect on loyalty p-values ​​0.015. Individual character influences loyalty with p-values ​​0.002. Job satisfaction affects loyalty with p-values ​​0.001. Indirectly, job satisfaction mediates between motivation and loyalty with p-values ​​of 0.038. Job satisfaction mediates between the influence of individual character on loyalty p-values ​​0.040.